Phenological aspects of Syngonanthus elegans (Bong.) Ruhl. (Eriocaulaceae) from Serra do Cipo - MG. Brazil - Scatena, V. L.; Lima, AAA; de Lemos, J. P. (Inst Tecnologia Parana, 1997)
S. elegans (Eriocaulaceae) is known in Brazil as star flower and is used economically for ornamental purposes. The fact that there is no control over its collection, brings about great damage to its population. Thus the importance of phenologic data for the conservation of the species. This paper reports the marking of 60 individuals in three different phases of development and the collection of monthly data about their phenology. S. elegans is a perennial plant with a rhizomatous stem that characterizes its vegetative growth. The pubescent leaves present in plants can prevent heat loss and their pigments can raise the ultra-violet radiation absorption. The young leaves present in plants during the begining of the dry season use rhizome reserves. Hydric scarcity may be the main reason for the mortality of the species. Vegetative growth and sexual reproduction are very important for the population's survival.,The blooming period in S. elegans occurs from om February to July and the dispersal of seeds occurs from August to December.
Keywords: phenology; Syngonanthus elegans; Eriocaulaceae